Analisis Wacana Kritis: Perilaku Bullying dalam Film Kenapa Gue? di Aplikasi Video: Critical Discourse Analysis: Bullying Behavior in the Film Kenapa Gue? on the Video App - Hidayat, Hilda Ramadhita; Rohmadi, Muhammad (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2024)
This study aims to present and reveal the meanings of the impact of bullying as depicted in the film "Kenapa Gue?" through Van Dijk's critical discourse analysis approach. The film portrays bullying in a university environment that leads to suicide. This research employs a descriptive-qualitative method by watching the film and analyzing it using the macrostructure, superstructure, and microstructure of Van Dijk's model. In the film "Kenapa Gue?", the macrostructure that can be derived from the film is social media in general. The superstructure of the film is the conflict that is organized sequentially. As for the microstructure in the film "Kenapa Gue?", it includes the two aspects of social media used for bullying, namely from the perspective of the perpetrator in the bullying content and the audience of such content. The results of the study indicate that this film reflects social issues relevant to technological advancements, particularly in the context of cyberbullying and the wise use of social media to avoid prolonged negative impacts. This analysis also emphasizes that the discourse in the film has a significant impact on public understanding of the consequences of bullying and the importance of social support in preventing it.